ANALISIS PENGARUH LEADER-MEMBER EXCHANGE TERHADAP KINERJA KARYAWAN DENGAN PARTISIPASI DAN WORK ENGAGEMENT SEBAGAI VARIABEL MEDIASI (Studi pada Karyawan PDAM Tirta Moedal Kota Semarang) - Alikasari, Meizza Jauza; Suharnomo, Suharnomo (Diponegoro Journal of Management, 2017)
Competition in the business world today can provide a competitive advantage needed the role of workers in order to improve the goals of the company. And also the relationship of superiors and subordinates make the foundation to be able to run every task given well to improve the performance of both. The purpose of this study is to analyze the influence of leader-member exchange on employee performance with participation and work engagement as a mediation variable.Case study conducted in this research is at PDAM Tirta Moedal Kota Semarang. The data collected in this study using questionnaires distributed to respondents and samples used in this study is simple random sampling with total samples of 105 respondents. Variable leader-member exchange as independent variable, and participation and work engagement as mediation or intervening variable, and employee performance variable as dependent variable. Data analysis techniques use path analysis, reliability test, validity test, classical assumption test, t test, F test, and sobel test to test the mediation effect of the variable.            The results of the analysis data using the path analysis that: 1.) LMX directly related and positive impact on participation, 2.) LMX directly related and positive impact on work engagement, 3.) participation directly related and positif impact on job performance, 4.) work engagement directly related and positif impact on job performance, and 5.) LMX directly related and positif impact on job performance.